The decline of beneficial insects in a fragmented temperate forest landscape: the case of beetles and the green gold in Mexico - Paloma Cambrón-Villalobos; Yurixhi Maldonado-López; Marcilio Fagundes; Ken Oyama; Pablo Cuevas-Reyes (European Journal of Soil Biology, 2026)

Vegetation structural parameters affect leaf litter decomposition along a secondary successional chronosequence in tropical dry forest - Jhonathan de Oliveira Silva; Maria Fernanda Gonçalves Durães; Priscyla Maria Silva Rodrigues; Pablo Cuevas-Reyes; Ricardo Luiz Louro Berbara; Mário Marcos do Espírito-Santo (Journal of Arid Environments, 2025)

Interplay of ant defense and leaf functional traits determine herbivory and fluctuating asymmetry during ontogeny of a myrmecophytic tropical plant - Joan Sebastian Aguilar-Peralta; Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Mário M. Espírito-Santo; Ken Oyama; Maurício L. Faria; Magno Augusto Zazá Borges; Marcílio Fagundes; G. Wilson Fernandes; Jean Carlos Santos; Pablo Cuevas-Reyes (Flora, 2025)

Plant‐herbivore interactions in Atlantic Forest: A dataset of host plants and their gall‐inducing insects - Jean Carlos Santos; Guilherme Ramos Demetrio; Henrique Venâncio; Fernanda Cristina Franco Cintra; Maria Virginia Urso‐Guimarães; Valéria Cid Maia; Walter Santos de Araújo; Pablo Cuevas‐Reyes; Wanessa Rejane de Almeida; Guilherme Magalhães Viana (Ecology, 2025)
Galls play a significant role in the plant–insect interactions in various ecosystems worldwide. Consequently, research on gall‐inducing insects and their host plants has garnered considerable attention in recent years, with a wealth of uncompiled data. This dataset, comprising 2,059 records of 868 native species, 361 genera, and 106 families of host plants, provides valuable information regarding the Atlantic Forest biome, one of the world's most important rainforests. The five most common botanical families represented in the dataset are Myrtaceae, Asteraceae, Fabaceae, Melastomataceae, and Rubiaceae, accounting for 40.41% of all records and 40.21% of the total number of species. In addition, exotic host plant species from families such as Anacardiaceae, Asteraceae, Fabaceae, Myrtaceae, and Verbenaceae are presented. The dataset also includes 204 species of gall‐inducing insects, with a large predominance of Diptera (189 species), followed by seven species of Hemiptera, four species of Lepidoptera, and two species each of Coleoptera and Thysanoptera. This study is the first to compile inventories of plant‐galling insect communities and information on the diversity and distribution of insect galls and their host plants in the Atlantic Forest. The dataset highlights areas for further research on patterns of diversity and distribution and offers a foundation for developing and testing new ecological hypotheses. Researchers are encouraged to cite this data paper when utilizing the information in their publications and to inform us of the application of the data. No copyright restrictions were applied to the dataset.

Tri-trophic networks of oak gall-inducing-insects and their parasitoids in Mexican avocado agrosystems: Forest coverage and local climatic variables importance - Icauri Sofía Prieto-Dueñas; Pablo Cuevas-Reyes; Marcela Sofía Vaca-Sánchez; Ken Oyama; Walter Santos de Araújo; Magno Augusto Zazá Borges; Marcílio Fagundes; G․Wilson Fernandes; Yurixhi Maldonado-López (Ecological Complexity, 2025)

Set fire to the gall: Can the gall protect the galling weevil from fire? - Jean Carlos Santos; Henrique Venâncio; Guilherme Ramos Demetrio; Wanessa Rejane de Almeida; Walter Santos de Araújo; Pablo Cuevas‐Reyes (Ecology, 2025)

Land-use change from native forest to avocado orchards: Effects on soil nutrient transformation and microbial communities - Brenda Baca-Patiño; Antonio González-Rodríguez; Felipe García-Oliva; Ariana García; Ingrid Lara-De La Cruz; Roberto Garibay-Orijel; Amisha Poret-Peterson; Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Alberto Gómez-Tagle; Yunuen Tapia-Torres (Applied Soil Ecology, 2025)

Vulnerability of seedlings to herbivore and pathogen attack: the importance of plant vigor and plant nutritional quality in Hymenaea courbaril - G. Wilson Fernandes; Letícia Ramos; Jean Carlos Santos; Ramón Perea; Rennan Garcias Moreira; Pablo Cuevas-Reyes; Rodolfo Dirzo (Arthropod-Plant Interactions, 2024)

Importance of abiotic factors in shaping canopy arthropod assemblages: the case of Quercus castanea Née (Fagales:Fagaceae) a Mexican endemic oak - Pablo Cuevas-Reyes; Marcela Sofía Vaca-Sánchez; Ken Oyama; G. Wilson Fernandes; Francisco Javier Loera-Padilla; Ma. Carmen López-Maldonado; Marcílio Fagundes; Maurício Lopes de Faria; Magno Augusto Zazá Borges; Yurixhi Maldonado-López (European Journal of Forest Research, 2024)

Species richness and network topology patterns in Neotropical plant-galling communities changes along an urbanization gradient - Walter Santos de Araújo; Kelly Christie dos Santos Costa; Érica Vanessa Durães Freitas; Jean Carlos Santos; Pablo Cuevas-Reyes (Journal of Insect Conservation, 2024)

Functional leaf-trait variability and herbivory in oaks along a Mexican avocado agrosystem mosaic - Marcela Sofía Vaca-Sánchez; Mário M. Espírito-Santo; Yurixhi Maldonado-López; Ken Oyama; Abel Pérez-Solache; Maurício Lopes de Faria; Magno Augusto Zazá Borges; G. Wilson Fernandes; Pablo Cuevas-Reyes (Flora, 2024)

Diversity patterns of host plants and their gall-inducing insects in the Brazilian Cerrado: testing ecological and historical hypotheses - Fernanda C. F. Cintra; Valéria C. Maia; Maria V. Urso-Guimarães; Walter S. de Araújo; Marco A. A. Carneiro; Henrique Venâncio; Wanessa R. de Almeida; Janete F. Andrade; Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Jean C. Santos (Arthropod-Plant Interactions, 2023)

Patterns in Wing Morphology and Fluctuating Asymmetry in Eulaema nigrita along an Altitudinal Gradient in the Brazilian Rupestrian Grassland - Marcela Sofía Vaca-Sánchez; Pablo Cuevas-Reyes; Israel Munck; Yumi Oki; Natalia Moia; Thamires Freitas; Aline Almeida; Kamilla Castelan; Geraldo Wilson Fernandes (Neotropical Entomology, 2023)

Changes in herbivory patterns and insect herbivore assemblages associated to canopy of Quercus laurina: importance of oak species diversity and foliar chemical defense - Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Ken Oyama; Guillermo Delgado; Joan Sebastian Aguilar-Peralta; Magno Augusto Zazá Borges; Maurício Lopes de Faria; Marcílio Fagundes; Ma. Carmen López-Maldonado; Pablo Cuevas-Reyes (Trees, 2023)

Guild-dependent effects of forest fragmentation in canopy arthropod diversity associated to Quercus deserticola - Silvia Ecaterina García-Jain; Yurixhi Maldonado-López; Ken Oyama; Ma. Carmen López-Maldonado; Marcílio Fagundes; Maurício Lopes de Faria; Mário M. Espírito-Santo; Marcela Sofía Vaca-Sánchez; Pablo Cuevas-Reyes (European Journal of Forest Research, 2023)

Changes in land use of temperate forests associated to avocado production in Mexico: Impacts on soil properties, plant traits and insect-plant interactions - Abel Pérez-Solache; Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Maurício Lopes De Faria; Magno Augusto Zazá Borges; Marcílio Fagundes; Ken Oyama; María Isabel Méndez-Solórzano; Joan Sebastian Aguilar-Peralta; Rafael Hernández-Guzmán; Pablo Cuevas-Reyes (Agricultural Systems, 2023)

Quantitative trophic networks of insect gallers and their parasitoids in the hybrid oak complex Quercus magnoliifolia x Quercus resinosa - Yurixhi Maldonado-López; Walter Santos de Araújo; Antonio González-Rodríguez; Ken Oyama; Marcilio Fagundes; Cecilia Diaz-Castelazo; Karina Sánchez-Echeverría; Magno Borges; Griselda Pérez-López; Pablo Cuevas-Reyes (Arthropod-Plant Interactions, 2022)

Effects of forest fragmentation on plant quality, leaf morphology and herbivory of Quercus deserticola: is fluctuating asymmetry a good indicator of environmental stress? - Silvia Ecaterina García-Jain; Yurixhi Maldonado-López; Ken Oyama; Marcílio Fagundes; Maurício Lopes de Faria; Mário M. Espírito-Santo; Pablo Cuevas-Reyes (Trees, 2022)

Contrasting successional stages lead to intra- and interspecific differences in leaf functional traits and herbivory levels in a Mexican tropical dry forest - Joan Sebastian Aguilar-Peralta; Yurixhi Maldonado-López; Mário M. Espírito-Santo; Ricardo Reyes-Chilpa; Ken Oyama; Marcilio Fagundes; Luis Daniel Ávila-Cabadilla; Mariana Yolotl Álvarez-Añorve; Marcela Sofía Vaca-Sanchéz; Pablo Cuevas-Reyes (European Journal of Forest Research, 2022)

Canopy arthropod diversity associated with Quercus laurina: importance of an oak species diversity gradient on abundance, species richness and guild composition - Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Antonio González-Rodríguez; Ken Oyama; G. Wilson Fernandes; Marcílio Fagundes; Edmundo Carlos López-Barbosa; Joan Sebastian Aguilar-Peralta; Pablo Cuevas-Reyes (Journal of Insect Conservation, 2021)

Genetic and functional leaf traits variability of Quercus laurina along an oak diversity gradient in Mexico - Marcela Sofía Vaca-Sánchez; Antonio González-Rodríguez; Yurixhi Maldonado-López; Ken Oyama; Maurício Lopes de Faria; Marcílio Fagundes; Pablo Cuevas-Reyes (European Journal of Forest Research, 2021)

Variation in the co-occurrence of pathogen and herbivores between ontogenetic stages of Miconia albicans - Ana Carolina Costa Santos; Wanessa Rejane de Almeida; Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Jean Carlos Santos (Trees, 2021)

Soil resource availability, plant defense, and herbivory along a successional gradient in a tropical dry forest - Jhonathan O. Silva; Herbert Souza-Silva; Priscyla M. S. Rodrigues; Pablo Cuevas-Reyes; Mário M. Espírito-Santo (Plant Ecology, 2021)

Contrasting patterns of morphology, fluctuating asymmetry and leaf herbivory in three plant species of different successional stages of a tropical dry forest - Joan Sebastian Aguilar-Peralta; Antonio González-Rodríguez; Yurixhi Maldonado-López; Marcílio Fagundes; Maurício L. Faria; Luis Daniel Ávila-Cabadilla; Mariana Yolotl Álvarez-Añorve; Pablo Cuevas-Reyes (Trees, 2020)

Leaf herbivory and fluctuating asymmetry as indicators of mangrove stress - Yurixhi Maldonado-López; Marcela Sofía Vaca-Sánchez; Armando Canché-Delgado; Silvia Ecaterina García-Jaín; Antonio González-Rodríguez; Tatiana Cornelissen; Pablo Cuevas-Reyes (Wetlands Ecology and Management, 2019)

Functional attributes of two Croton species in different successional stages of tropical dry forest: effects on herbivory and fluctuating asymmetry patterns - José Gerardo González-Esquivel; Pablo Cuevas-Reyes; Antonio González-Rodríguez; Luis Daniel Ávila-Cabadilla; Mariana Yolotl Álvarez-Añorve; Marcilio Fagundes; Yurixhi Maldonado-López (Tropical Ecology, 2019)

Community structure of gall-inducing insects associated with a tropical shrub: regional, local and individual patterns - Ritiely Durães Coutinho; Pablo Cuevas-Reyes; G. Wilson Fernandes; Marcílio Fagundes (Tropical Ecology, 2019)

Hybridization increases canopy arthropod diversity in the Quercus affinis × Quercus laurina complex - Yurixhi Maldonado-López; Marcela Sofía Vaca-Sánchez; Antonio González-Rodríguez; Ken Oyama; Edmundo López-Barbosa; Marcilio Fagundes; Pablo Cuevas-Reyes (Journal of Insect Conservation, 2018)

A morphological database for 606 Colombian bird species - Paola Montoya; Mailyn A. Gonzalez; Elkin A. Tenorio; Juan Pablo López‐Ordóñez; Alejandro Pinto Gómez; Diego Cueva; Aldemar A. Acevedo Rincón; Camilo Angarita Yanes; Héctor Manuel Arango Martínez; Orlando Armesto; Jefry S. Betancur; Angela Caguazango Castro; et al. (Ecology, 2018)
Colombia is the country with the highest bird diversity in the world. Despite active research in ornithology, compelling morphological information of most bird species is still sparse. However, morphological information is the baseline to understand how species respond to environmental variation and how ecosystems respond to species loss. As part of a national initiative, the Instituto Alexander von Humboldt in collaboration with 12 Colombian institutions and seven biological collections, measured up to 15 morphological traits of 9,892 individuals corresponding to 606 species: 3,492 from individuals captured in field and 6,400 from museum specimens. Species measured are mainly distributed in high Andean forest, páramo, and wetland ecosystems. Seven ornithological collections in Colombia and 18 páramo complexes throughout Colombia were visited from 2013 to 2015. The morphological traits involved measurements from bill (total and exposed culmen, bill width and depth), wing (length, area, wingspan, and the distance between longest primary and longest secondary), tail (length and shape), tarsus (length), hallux (length and claw hallux), and mass. The number of measured specimens per species was variable, ranging from 1 to 321 individuals with a median of four individuals per species. Overall, this database gathered morphological information for >30% of Colombian bird diversity. No copyright, proprietary, or cost restrictions apply; the data should be cited appropriately when used.

Effects of ferric soils on arthropod abundance and herbivory on Tibouchina heteromalla (Melastomataceae): is fluctuating asymmetry a good indicator of environmental stress? - Pablo Cuevas-Reyes; Geanne Carla Novais Pereira; Irene Gélvez-Zúñiga; G. Wilson Fernandes; Henrique Venâncio; Jean Carlos Santos; Yurixhi Maldonado-López (Plant Ecology, 2018)

Effects of herbivory and mistletoe infection by Psittacanthus calyculatus on nutritional quality and chemical defense of Quercus deserticola along Mexican forest fragments - Pablo Cuevas-Reyes; Griselda Pérez-López; Yurixhi Maldonado-López; Antonio González-Rodríguez (Plant Ecology, 2017)

Effects of plant hybridization on the structure and composition of a highly rich community of cynipid gall wasps: the case of the oak hybrid complex Quercus magnoliifolia x Quercus resinosa in Mexico - Griselda Pérez-López; Antonio González-Rodríguez; Ken Oyama; Pablo Cuevas-Reyes (Biodiversity and Conservation, 2016)

Diversity of gall wasps (Hymenoptera: Cynipidae) associated with oak trees (Fagaceae: Quercus) in a fragmented landscape in Mexico - Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Ken Oyama (Arthropod-Plant Interactions, 2016)

Patterns of infection by intestinal parasites in sympatric howler monkey (Alouatta palliata) and spider monkey (Ateles geoffroyi) populations in a tropical dry forest in Costa Rica - Selene Maldonado-López; Yurixhi Maldonado-López; Alberto Gómez-Tagle Ch.; Pablo Cuevas-Reyes; Kathryn E. Stoner (Primates, 2014)

Growth, plant quality and leaf damage patterns in a dioecious tree species: is gender important? - Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Gumersindo Sánchez-Montoya; Ken Oyama; Mauricio Quesada (Arthropod-Plant Interactions, 2014)

Tri-trophic interactions among congeneric sympatric host plants of Chamaecrista, seed predators and parasitoids - João A. Madeira; G. Wilson Fernandes; Antonio González-Rodríguez; Pablo Cuevas-Reyes (Arthropod-Plant Interactions, 2013)

Comparing galling insect richness among Neotropical savannas: effects of plant richness, vegetation structure and super-host presence - Walter Santos de Araújo; Claudia Scareli-Santos; Frederico Augusto Guimarães Guilherme; Pablo Cuevas-Reyes (Biodiversity and Conservation, 2013)

Species richness of gall-forming insects in a tropical rain forest: correlations with plant diversity and soil fertility - Pablo Cuevas-Reyes; Cristina Siebe; Miguel Martínez-Ramos; Ken Oyama (Biodiversity and Conservation, 2003)